The Effects of Combination Treatment Using Phenoxodiol and Docetaxel, and Phenoxodiol and Secreted Frizzled-related Protein 4 on Prostate Cancer Cell Lines - Mahoney, S.; Arfuso, Frank; Millward, M.; Dharmarajan, Arunasalam (OMICS Publishing Group, 2014)
Although much progress has been made for the treatment of prostate cancer, patients with advanced prostate cancer still have a poor 5 year survival rate. Current practices for hormone-refractory/castrate resistant, metastatic prostate cancer involve the use of taxanes. Docetaxel, in particular, is being incorporated in numerous current clinical trials either as a single or combination agent against androgen-independent prostate cancer. Combination therapies have the potential to increase the effectiveness of drug treatments while simultaneously increasing quality of life by reducing side effects, lowering effective dosage rates, or by increasing effectiveness of one compound once combined with another. Using three diverse human prostate cancer cell lines, LNCap, DU145, and PC3, we studied the effect of the novel prostate cancer drug phenoxodiol in combination with docetaxel by utilizing isobolograms, and found that docetaxelinduced cell death was attenuated by co-treatment or pre-treatment of cells with phenoxodiol. This attenuation is associated with the prevention of cells from entering the G2/M phase of the cell cycle where docetaxel is functional in damaging the spindle fibers, and potentially due to p21WAF1 mediated cell survival after docetaxel treatment.We also investigated the use of the Wnt signaling pathway antagonist secreted frizzled-related protein 4 (sFRP4) to increase the effectiveness of phenoxodiol treatment. We found that, through stabilization of the GSK3β molecule, sFRP4 induces degradation of active β-catenin, which causes an increased sensitivity to isoflavone cytotoxic induction by increasing p21WAF1 expression and decreasing expression of c-Myc, Cyclin-D1, and other potent oncogenes. Phenoxodiol induces significant cytotoxicity when combined with a Wnt/β-catenin receptor blocker such as sFRP4. This promotes the concept that combination therapy of a Wnt inhibitor with phenoxodiol might increase the effectiveness of phenoxodiol and give a subset population of prostate cancer sufferers a more effective treatment regime.